Proceedings of the seminar-workshop on breeding and seed production of cultured finfishes in the Philippines : (Aquaculture Department Southeast Asian Fisheries Development Center, 1996)
The seminar-workshop on breeding and seed production of cultured finfishes in the Philippines : to promote the exchange of information and views among scientists and technicians on breeding and seed production of various finfishes.